Duration of Breastfeeding and Risk Reduction of Breast Cancer among Mothers Who Have Ever Breastfed: A Case-Control Study Conducted in Bahir Dar, Ethiopia - Fentanesh Nibret Tiruneh; Peter Austin Morton Ntenda (Wiley, 2024)
Introduction. Breast cancer is currently the most frequently detected cancer in women and the primary cause of cancer-related deaths globally. The incidence of breast cancer has significantly increased in countries across sub-Saharan Africa, counting Ethiopia. There are multiple determinants of breast cancer, a few of these can be changeable whereas others are not. Evidence suggests that breastfeeding, which is a changeable determinant, reduces breast cancer risk. However, there is a lack of evidence specifically linking the duration of breastfeeding to breast cancer risk. To date, no study has been conducted on the association between the duration of breastfeeding and the likelihood of breast cancer among Ethiopian women. Objective. The aim of this study was to evaluate the relationship between breastfeeding duration and breast cancer risk in Ethiopian mothers who had breastfed, taking into account other significant determinants. Methods. A hospital-based case-control study was carried out in Bahir Dar, Ethiopia, involving 203 women (70 cases and 133 controls). Face-to-face interviews were performed using a standardized, validated questionnaire that assessed various sociodemographic, reproductive, lifestyle, and dietary characteristics. Differences between cases and controls were evaluated using the chi-square test. The associations among factors were examined through bivariate and multivariable binary logistic regression, with results presented as odds ratios and 95% confidence intervals. Results. The multivariable investigation revealed that an inverse relationship between breastfeeding duration and breast cancer risk. Mothers who breastfed for a longer period had a 93% lower risk of breast cancer (AOR = 0.07; 95% CI: 0.021-0.21) compared to those who breastfed for a shorter duration. Younger mothers had a 95% lower likelihood of developing breast cancer (AOR = 0.05; 95% CI: 0.003-0.91) than older mothers. Additionally, mothers with sedentary behaviour were 10.53 times more likely to develop breast cancer (AOR = 10.53; 95% CI: 5.21-21.36) than those who were moderately or highly active. Mothers who experienced chest therapy were 6.43 times more likely to develop breast cancer (AOR = 6.43; 95% CI: 3.20-13.90) compared to those who had not. Conclusions. Interventions such as breastfeeding counselling and promoting the recommended duration of breastfeeding are crucial in minimizing the risk of breast cancer. Enhancing physical activity should also be viewed as a vital approach for lowering breast cancer risk. Additionally, healthcare professionals need to limit exposure to chest radiation therapy to reduce the likelihood of breast cancer.